Intimate partner violence as a factor in contraceptive discontinuation among sexually active married women in Nigeria - KUPOLUYI, Joseph Ayodeji (BMC Womens Health, 2020)
BACKGROUND: In spite of the well-established associations between socioeconomic and demographic factors and the high rate of contraceptive discontinuation among sexually active married contraceptive users, little is known in Nigeria about the relationship between contraceptive discontinuation and sexually active married women who have experienced Intimate Partner Violence (IPV). METHODS: The 2013 Nigeria Demographic and Health Survey data on women’s reproductive calendars and domestic violence were used to investigate the relationship between IPV and contraceptive discontinuation in a year period. A weighted sample size of 1341 women in a union in the domestic violence module, who have experienced IPV, and are using any contraceptive and are not sterilized in the 12 months periods was analyzed using frequency tables and chart, Pearson’s chi-square test, and binary logistic regression model. RESULTS: The results showed that women who have experienced any type of IPV are 1.28 times more likely to have discontinued contraceptive use although they are still at risk of becoming pregnant (aOR = 1.28, CI: 1.15–1.91; p < 0.05) than those who have not experienced IPV. The tertiary level of education (aOR = 3.94, CI = 1.67–9.29; p < 0.05), unemployed status (aOR = 1.97, CI = 1.07–3.62; p < 0.05), and higher marital duration of 20 years and above (aOR = 4.89, CI = 2.26–10.57; p < 0.05) significantly influenced women who have experienced any types of IPV to discontinue contraceptives even though they are still at risk of becoming pregnant than those who have not experienced IPV. CONCLUSION: The study revealed that women who have experienced any form of IPV were significantly influenced by their education, occupation, the number of living children, and marital duration to discontinue contraception while still at risk of becoming pregnant. Thus, the study concludes that intervention programmes aimed at increasing contraceptive prevalence rate should be mindful of IPV which may affect women’s use of contraceptives.